DNA isolation of potentially probiotic lactic acid bacteria from durian arilus fermentation (jruek drien) - Yulia Sari Ismail; Cut Yulvizar; Risa Riani Ramlan; Mahyuddin (Current Research on Bioscences and Biotechnology, 2019)
Jruek drien is an Acehnese traditional fermented food containing lactic acid bacteria (LAB) from durian arilus fermentation. Lactic acid bacteria from jruek drien were considered as potential probiotics. The LAB from jruek drien were first identified by phenotyping and genotyping analysis. The aim of the research is to isolate DNA from lactic acid bacteria (JD-2 and JD-3) from jruek drien for identification based on 16S rDNA gene sequence analysis. The research steps consist of samples regeneration in MRSA medium with temperature of incubation at 37°C, samples culturing in TSB medium, DNA isolation, and measurement of the DNA concentration and DNA purity using nanophotometer. The result showed that the JD-2 and the JD-3 isolates grow well on selective media MRSA by incubation temperature at 37°C. JD-2 has a DNA concentration of 40.0 ng/μl with a purity level of 2.0, and JD-3 has a DNA concentration of 32.5 ng/μl with a purity level of 1.8 at the A260/A280 ratio. The 16S rRNA gene of JD-2 isolate was successfully amplified at 1426 bp and JD-3 isolate at 1435 bp. The JD-2 isolate was identified as Bacillus subtilis because it has the highest similarity with Bacillus subtilis strain WA3-4. The JD-3 isolate was identified as Lactobacillus plantarum because it has the highest similarity with L. plantarum strain CSI9 and strain CSI3.